Genetic Parameter Estimation on Upland Rice Agronomic Characters in Ultisols through Diallel Analysis - MARIA AGUSTINA; SURJONO HADI SUTJAHJO; TRI KOESOEMANINGTYAS; YUSURUM JAGAU (HAYATI Journal of Biosciences, 2005)
An estimate of genetic parameters was made to study the types of gene action in rice. A half diallel analysis was performed among seven rice genotypes with different genetical backgrounds, i.e. Situgintung, Jatiluhur, Gajah Mungkur, B8503E-TB-9-0-3, Krowal, CT6510-24-1-3, IR 64, and its 21 progenies. This experimental material was arranged in a complete block design with four replications. All observed characters had highly significant genotypic differences. The genetic parameters were estimated following Hayman method. The simple model of additive-dominance was sufficiently detected through the absence of nonalellic interaction. Productive tillers exhibited partial dominance. Heritability in a narrow sense was high. There was a positive correlation between grain yield and the number of productive tillers.